PENANGANAN BALITA GIZI BURUK SECARA RAWAT JALAN DI PUSKESMAS DENGAN PEMBERIAN MAKANAN TERAPI : FORMULA-100 DAN READY TO USE THERAPEUTIC FOOD (OUT-PATIENT TREATMENT OF SEVERE MALNOURISHED CHILDREN AT HEALTH CENTER WITH THERAPEUTIC FOOD : FORMULA-100 AND RE - Astuti Lamid; Anies Irawati; Arnelia Arnelia (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT The study of outpatient treatment of severe malnourished children with therapeutic food: Formula-100 (F-100) and Ready To Use Therapeutic Food (RUTF) had been conducted. The purpose was to optimize the growth of severe malnourished children. Formula-100, milk-based, has been used in health centers. While RUTF, lipid based, has been widely used to improve the nutritional status of severe malnourished children in African countries. The design of this study was quasi experiment and located in ten health centers in Bogor and Subang Regency. Samples were severe malnutrition children, aged 10-54 months with Weight (W) / Height (H) indicator <-3,0 Z-scores or W/H <-2,0 Z-scores with clinical signs of severe malnutrition. There were two treatment groups: F-100 and RUTF which were given to 39 children in each group for 6 weeks. Data collected were anthropometric, consumption of nutrients, diseases and socio-economics aspects, then data were analyzed using t test. Result showed that before treatment the mean of W/H both groups were <-3,0 Z-scores which catagorized as severe wasted, while after treatment the mean became >-3,0 Z-scores which was catagorized wasted. The improvement of nutritional status (W/H) between the RUTF and F-100 group were not significantly different (p>0,05). Almost all of nutrients consumption in both groups fulfilled the recommended dietary allowances, and the nutrient adequancy in both groups were not significantly different after treatment (p>0,05). Therefore RUTF can be used as alternative of F-100. The advantages of RUTF were lower price and containedmore vitamines and minerals compared to F-100. Keywords: malnutrition, wasted, outpatient, Ready to Use Therapeutic Food ABSTRAK Penelitian penanganan balita gizi buruk secara rawat jalan di Puskesmas dengan pemberian makanan terapi Formula-100 (F-100) dan Ready to Use Therapeutic Food (RUTF) telah dilakukan. Tujuannya adalah untuk mengoptimalkan pertumbuhan balita gizi buruk. Formula-100, berbahan dasar susu, telah digunakan di Puskesmas. Sedangkan RUTF, berbentuk pasta, telah digunakan di negara-negara Afrika dan berhasil memperbaiki status gizi balita gizi buruk. Desain penelitian pada studi ini adalah kuasi eksperimen yang  berlokasi di 10 Puskesmas di Kabupaten Bogor dan Subang. Sampel adalah balita gizi buruk umur 10-54 bulan dengan indikator BB/PB <-3,0 Z-skor atau BB/PB <-2,0 Z-skor dengan tanda klinis gizi buruk. Terdapat dua kelompok makanan terapi, F-100 dan RUTF yang diberikan kepada 39 anak di dalam setiap grup selama 6 minggu. Data yang dikumpulkan adalah antropometri, konsumsi zat gizi, sosial ekonomi dan penyakit. Data dianalisis menggunakan uji-t. Hasil penelitian menunjukkan rata-rata status gizi awal pada kedua kelompok <-3,0 Z-skor yang dikategorikan sangat kurus, setelah intervensi rata-rata status gizi meningkat menjadi >-3,0 Z-skor yang dikategorikan kurus. Perbaikan status gizi antara kedua kelompok tidak berbeda bermakna (p>0,05). Hampir semua konsumsi zat gizi kedua kelompok mencapai Angka Kecukupan Gizi yang dianjurkan, dan konsumsi zat gizi kedua kelompok tidak berbeda bermakna setelah intervensi (p>0,05). Dengan demikian, RUTF dapat digunakan sebagai alternatif selain F-100. Keunggulan RUTF adalah harga lebih murah dan lebih banyak mengandung vitamin, dan mineral dibandingkan dengan F-100. [Penel Gizi Makan 2012, 35(2): 168-181] Kata kunci: gizi buruk, kurus, rawat jalan, Ready to Use Therapeutic Food